Assessment of river plan change using RS and GIS technique - Mohd Khairul Amri, Kamarudin; Azman, Azid; Roslan, Umar (Penerbit UTM Press, 2015)
Rivers is one of the complex natural systems. Classification of the river plan change is very important to know the river problems in early stage, where the classification database can help to understand the behavior of the river in each part. This article discusses about the classification of river plan change at the mainstream of Pahang River, Malaysia. Based on Geographical Information System (GIS) and Remote Sensing (RS) database, analysis of Types Of Lateral Activity (TYLAT) method and Modes of Meander Movement (MOME) method have been used to identify the evolution of the river plan change. The study results indicated, methods of TYLAT are more suitable to use for examining the evolution of river plan change for large and width rivers. While, method of analysis MOME index is more suitable for smaller types of rivers as the upper and middle reaches of the river. From this result, this study can be produced the basic information or database to understanding the characteristics or behavior parts in parts of the main Pahang River. This result also is very important to local authorities to know the early river problems in this area.